2021
DOI: 10.1016/j.nbd.2020.105245
|View full text |Cite
|
Sign up to set email alerts
|

Brain pathology caused in the neonatal macaque by short and prolonged exposures to anticonvulsant drugs

Abstract: Barbiturates and benzodiazepines are potent GABA A receptor agonists and strong anticonvulsants. In the developing brain they can cause neuronal and oligodendroglia apoptosis, impair synaptogenesis, inhibit neurogenesis and trigger long-term neurocognitive sequelae. In humans, the vulnerable period is projected to extend from the third trimester of pregnancy to the third year of life. Infants with seizures and epilepsies may receive barbiturates, benzodiazepines and their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…However, caution should be urged at this juncture as the data on antiepileptic medications in the preterm population are limited and primarily retrospective in nature. This concern is further highlighted by the neurodevelopmental risks associated with use of antiepileptic drugs in neonates ( 56 ), specifically phenobarbital ( 57 , 58 ), the conventional first-line seizure treatment. While phenobarbital remains the most commonly used treatment ( 2 , 59 ), treatment failure rates as high as 63% have been reported ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, caution should be urged at this juncture as the data on antiepileptic medications in the preterm population are limited and primarily retrospective in nature. This concern is further highlighted by the neurodevelopmental risks associated with use of antiepileptic drugs in neonates ( 56 ), specifically phenobarbital ( 57 , 58 ), the conventional first-line seizure treatment. While phenobarbital remains the most commonly used treatment ( 2 , 59 ), treatment failure rates as high as 63% have been reported ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion fixation was performed with 4% paraformaldehyde in phosphate buffer by a trained pathologist according to institutional euthanasia standards. This is the same control group we used in previously published work ( Ikonomidou et al, 2019 ; Noguchi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interference with this neurotransmitter system may trigger adverse effects in the immature brain. Over the past two decades, we and many other investigators reported that compounds which positively modulate GABA A receptors, including barbiturates, benzodiazepines, alcohol and volatile anesthetics, trigger apoptosis of neurons and oligodendroglia in the rodent and nonhuman primate brain ( Ikonomidou et al, 2000 ; Brambrink et al, 2012 ; Brambrink et al, 2010 ; Noguchi et al, 2021 ), suppress neurogenesis ( Stefovska et al, 2008 ), inhibit normal synapse development and maturation ( Forcelli et al, 2012 ; Jevtovic-Todorovic et al, 2013 ) and cause long-lasting behavioral and cognitive impairments ( Fredriksson et al, 2007 ; Jevtovic-Todorovic et al, 2003 ; Stefovska et al, 2008 ; Paule et al, 2011 ), when exposure occurs during a period of rapid brain growth. In humans, this brain growth spurt period starts in the third trimester of gestation and extends to the third year of life ( Dobbing and Sands, 1979 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its unique properties for sedation, hypnosis, antianxiety, anterograde amnesia, and central muscle relaxation, and as an anticonvulsant, midazolam is among the top choices for managing sedation and epilepsy in children and adolescents (15)(16)(17)(18)(19)(20). Since the drug can be used repeatedly for an extended period of time, its potential negative effects on neural development has been previously evaluated (21)(22)(23)(24). It has been found that midazolam usage during puberty may affect brain development (25,26).…”
Section: Introductionmentioning
confidence: 99%